Aprender e ensinar na era digital: um estudo sobre Mobile Learning emexperiênciasde avaliação de aprendizagem na Educação Superior - BERWANGER, Perla Maria (2019)
Mobile digital technologies have rapidly integrated into the everyday lives of various societies and have become innovative resources for social practices in various dimensions, such as education. This investication approach the presence and the use of mobile digital technology in process of learning-teaching in a undergraduated course. As the given presence and how occure this usage, are the point that lead our study.A field research on the presence and use of mobile digital technologies in teaching-learning processes in an undergraduate course. How this presence occurs and how the use occurs are questions that guided our study. The research had as general objective to investigate the use of smartphone in the teaching-learning processes in the Administration course of UFMA specifically to a) to analyze the motivations of the teachers and students in situations of use and what their purposes, b) to verify if the use of the applications Kahoot!, GoSoapBox and Edpuzzle would bring positive and / or negative modifications during the process of teaching learning, and c) to identify the familiarity of these subjects on digital devices and mobile applications.The research used the cartographic method and is inserted in the convergence of two areas of knowledge, Administration and Education, and develops with an Interdisciplinary character. We rely on the theoretical elaborations of Siemens (2004, 2006); Prensky (2001, 2003, 2004); Santaella (2010, 2013); Moura (2010); Kenski (2012); Carvalho (2015); Coutinho (2013, 2010); Bottentuit Junior (2017), among others. Our exploratory-descriptive research adopted a mixed-quantitative and qualitative approach. The universe of our research is composed of 61 individuals(teachers and students) of the Administration course of the Federal University of Maranhão, Baganga Campus, in São Luís. We work with a non-probalistic sample for convenience. Data collection was performed between August and November of 2018. We used research diaries, observation sheets, multiple choice questionnaires and mixed questionnaires. In our experiences with the smartphonewe use three applications:Kahoot! GoSoapBox and Edpuzzle. The results indicate that the subjects participating in the research do not use smartphones and digital applications as a central didactic-pedagogical resource in the classroom. Some Technologies of Information and Communication are activated as facilitators of the management of activities and as secondary support in their routine didactic-pedagogical practices. Almost all students did not know the applications cited or their possibilities of use. Of ten applications presented, four were used in the disciplines Logistics and General Theory of Administration. We suggest other exploratory and descriptive investigations to deepen our understanding of the phenomenon. We suggest broadening the scope of the empirical field, to do so now as a comparative study among institutions of higher education in the state of Maranhão.